Intraoperative Ultrasound Appearance of a Pancreatic Cerebral Metastasis: A Case Report - Donofrio, Carmine Antonio; Barzaghi, Lina Raffaella; Capitanio, Jody Filippo; Cavalli, Andrea; Panni, Pietro; Snider, Silvia; Mortini, Pietro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Brain metastases (BMs) derived from pancreatic adenocarcinoma (PAC) have an extremely low incidence (0.1–0.4%) and are usually associated with a very poor prognosis. The treatment strategy is palliative and includes conventional radiotherapy, stereotactic radiosurgery, chemotherapy, and surgical resection.Case Description A 39-year-old man with a history of PAC developed a systemic tumor relapse with intracranial progression. Magnetic resonance imaging (MRI) documented a right rolandic, cortical, and cystic lesion with leptomeningeal intrasulcular extension. The intraoperative ultrasound (iUS) depicted a hyperechogenic area surrounding the anechogenic cystic lesion and allowed us to obtain gross total resection of the tumor.Conclusions To the best of our knowledge, we describe for the first time the iUS aspect of a pancreatic BM. In this case the use of iUS allowed us to increase the extent of resection and surgical safety, thus reducing the risk of new postoperative neurologic deficits.
Keywords: intraoperative ultrasound; pancreatic adenocarcinoma; metastasis; brain